Laboratory Model Test on The Sand Column for Reinforcement System of Flexible Pavement - Fajarwati, Yuli; Dian Eksana Wibowo; Endaryanta; Amalina, Anisa Nur (Teknisia, 2023)
Flexible pavement failures in Indonesia are primarily attributed to weak subgrade conditions, necessitating soil reinforcement measures. This study aimed to enhance soil-bearing capacity through soil reinforcement experiments utilizing a mixture of sand columns, rice husk ash, and cement. A prototype was constructed, including a 1×1×1 m steel box, an IWF steel frame, a dial gauge, a steel plate, and a proving ring, to apply a load to soil arranged within the iron box using a 3-ton hydraulic jack. The study focused on a clay soil type (following the AASHTO method) and conducted soil reinforcement in four scenarios. The result shows that in all scenarios involving a sand column, Scenario 1: 3% sand, 3% rice husk ash, and 6% cement obtained a qult is 0.23 kg/cm2 and BCR 114.94%; Scenario 2: 3% sand, 6% rice husk ash, and 3% cement obtained a qult is 0.12 kg/cm2 and BCR 11.49%; Scenario 3: 6% sand, 3% rice husk ash, and 3% cement obtained a qult is 0.14 kg/cm2 and BCR 26.44%; Scenario 4: 6% sand, 6% rice husk ash, and 0% cement obtained a qult is 0.24 kg/cm2 and a BCR of 116.09%. Notably, scenario 4, featuring a column composition of 6% sand, 6% rice husk ash, and 0% cement, achieved a significant increase in bearing capacity (qult) with a value of 0.24 kg/cm2 and a high Bearing Capacity Ratio (BCR) of 116.09%. Scenario 1 was the most effective in reducing moisture content by 4% relative to the original soil moisture content, with a mixture comprising 3% sand column, 3% rice husk ash, and 6% cement. The findings suggest that applying soil columns can enhance the performance of flexible pavements.